Construction of a risk scoring system using clinical factors and RYR2 polymorphisms for bleeding complications in patients on direct oral anticoagulants - Jang, Eun Jeong; Kim, Jung Sun; Choi, Seo A.; Yee, Jeong; Song, Tae-Jin; Park, Junbeom; Gwak, Hye Sun (Frontiers in Pharmacology, 2023)
Introduction: Bleeding is one of the most undesirable complications of direct oral anticoagulants (DOACs). While the ryanodine receptor (RYR2) has been related to cardiac diseases, research on bleeding complications is lacking. This study aimed to elucidate the association between RYR2 and bleeding risk to develop the risk scoring system in patients treated with DOACs.Methods: This study was a retrospective analysis of prospectively collected samples. We selected ten SNPs within the RYR2 gene, and two models were constructed (Model I: demographic factors only, Model II: demographic and genetic factors) in multivariable analysis. Independent risk factors for bleeding were used to develop a risk scoring system.Results: A total of 447 patients were included, and 49 experienced either major bleeding or clinically relevant non-major bleeding. In Model I, patients using rivaroxaban and experiencing anemia exhibited an increased bleeding risk after adjusting for covariates. Upon incorporating genetic factors into Model I, a significant association with bleeding was also observed in cases of overdosing on DOACs and in patients with a creatinine clearance (CrCl) <30 mL/min, in addition to rivaroxaban and anemia (Model II). Among genetic factors, RYR2 rs12594 GG, rs17682073 AA, rs3766871 GG, and rs6678625 T alleles were associated with bleeding complications. The area under the receiver operating characteristic curve (AUROC) of Model I was 0.670, whereas that of Model II increased to 0.803, demonstrating better performance with the inclusion of genetic factors. Using the significant variables in Model II, a risk scoring system was constructed. The predicted bleeding risks for scores of 0, 1-2, 3-4, 5-6, 7-8, and 9-10 points were 0%, 1.2%, 4.6%, 15.7%, 41.7%, and 73.3%, respectively. Conclusion: This study revealed an association between RYR2 and bleeding complications among patients taking DOACs and established a risk scoring system to support individualized DOAC treatment for these patients.